LINGUISTIC FEATURES OF FLOWER NAMES IN ENGLISH AND UZBEK LANGUAGES - Javliyev Mansurbek Odil o’g’li (Western European Studies, 2025)
This article explores the linguistic features of flower names in English and Uzbek languages from a comparative perspective. It examines the etymological roots, morphological structures, and semantic characteristics of selected flower names. The study also highlights cultural aspects influencing the naming traditions in both languages. The analysis aims to reveal both universal and culture-specific features in the linguistic representation of flowers, contributing to cross-linguistic and cultural understanding.
Keywords: flower names; comparative linguistics; etymology